2013
DOI: 10.1093/jjco/hys227
|View full text |Cite
|
Sign up to set email alerts
|

An Optimal mRNA Marker for OSNA (One-step Nucleic Acid Amplification) Based Lymph Node Metastasis Detection in Colorectal Cancer Patients

Abstract: We found that CK19 mRNA has the best diagnostic performance and its cut-off value for discriminating positive from negative lymph nodes can be set in the range of 75-500 copies/µl with 96.4% sensitivity and 100% specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…These findings confirm the technical feasibility of lymph node staging of colon carcinoma patients as recently described (Croner et al , 2010; Guller et al , 2012; Yamamoto et al , 2013). OSNA appears to be a more accurate method of staging colon carcinoma patients, and identifies pN0 individuals who may benefit from adjuvant treatment.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings confirm the technical feasibility of lymph node staging of colon carcinoma patients as recently described (Croner et al , 2010; Guller et al , 2012; Yamamoto et al , 2013). OSNA appears to be a more accurate method of staging colon carcinoma patients, and identifies pN0 individuals who may benefit from adjuvant treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Hence, methods are urgently needed that enable the investigation of the whole lymph node in a timely and feasible manner. OSNA is a novel molecular technology for CK19 mRNA-based identification of lymph node metastases in breast cancer and colorectal carcinomas (Tsujimoto et al , 2007; Croner et al , 2010; Yamamoto et al , 2011, 2013; Guller et al , 2012). The enormous advantage of this method is that the complete lymph node can be homogenised and transferred to OSNA without prior preparation, thus reducing the risk of potential contamination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we and other researchers have reported a new rapid gene detection system, One-Step Nucleic acid Amplification (OSNA), for lymph node metastasis detection in breast, colorectal, gastric, and lung cancer patients [21][22][23][24]. This method consists of a simple assay sample preparation and automated rapid gene detection using a reverse transcription loop-mediated amplification (RT-LAMP) method [25].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have further demonstrated the high sensitivity of OSNA in detecting LN metastasis of breast, gastric, lung, and colorectal cancers. [9][10][11][12][13][14][15][16] Our own previous prospective, multicenter studies conducted in Japan demonstrated the usefulness of the OSNA assay as a complementary tool for diagnosing LN metastasis and CRC staging. 17,18 The later study revealed that 17.6% (13/74) of patients with histologically node-negative stage II CRC were nodal positive by the OSNA assay.…”
mentioning
confidence: 99%